2010
DOI: 10.1021/cm903182n
|View full text |Cite
|
Sign up to set email alerts
|

Assemblies of Titanium Dioxide-Polystyrene Hybrid Nanoparticles for Dielectric Applications

Abstract: Macroscopic assemblies of hybrid nanoparticles composed of titanium dioxide core surrounded by covalently grafted polystyrene corona have been prepared by a combination of phosphonate coupling and "click" chemistry. The attached polymer chains existed in the brush regime, with grafting density inversely proportional to the degree of polymerization. Solution casting afforded preparation of robust films of the composite material where all the polymer chains were covalently bound to the uniformly distributed inor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 37 publications
4
123
0
Order By: Relevance
“…All nanocomposites were prepared with polystyrene, a non-polar polymer that exhibits relatively low breakdown strength (measured at 175 V/μm in this study) and relative permittivity (2.4 at 1 kHz), but maintains a low dielectric loss (ε′ = 10 titanate (BaTiO 3 ) nanoparticles, approximately 7.0 ± 1.5 nm in diameter, 23,24 were grafted with polystyrene (102 kg/mol M w ) following a previously reported procedure involving phosphonate coupling and click chemistry 18 ( Fig. 1a-c, see Supporting Information for full details).…”
Section: Experimental Materials and Synthesismentioning
confidence: 98%
See 1 more Smart Citation
“…All nanocomposites were prepared with polystyrene, a non-polar polymer that exhibits relatively low breakdown strength (measured at 175 V/μm in this study) and relative permittivity (2.4 at 1 kHz), but maintains a low dielectric loss (ε′ = 10 titanate (BaTiO 3 ) nanoparticles, approximately 7.0 ± 1.5 nm in diameter, 23,24 were grafted with polystyrene (102 kg/mol M w ) following a previously reported procedure involving phosphonate coupling and click chemistry 18 ( Fig. 1a-c, see Supporting Information for full details).…”
Section: Experimental Materials and Synthesismentioning
confidence: 98%
“…Tchoul et al reported that hairy PS@TiO 2 matrix free assemblies at 27% v/v inorganic loading have a relative dielectric constant of 6.4, compared to 2.4 for neat PS, while maintaining low dielectric loss similar to PS (tan δ = 0.04 at 1 kHz). 18 X-ray scattering demonstrated excellent particle dispersion with no visible clustering; thus, the deleterious effects of percolation that create conduction pathways and increase dielectric loss were avoided. 19 Similarly, Paniagua et al demonstrated that films of PMMA@BaTiO 3 HNPs achieved a maximum extractable energy density of 2 J/cc at intermediate loadings (22% v/v) -a twofold increase over a physically blended nanocomposite at comparable BaTiO 3 loading.…”
Section: Original Research Papermentioning
confidence: 99%
“…For lower graft densities, particle-polymer interactions responsible for packing frustrations of freely jointed chains at a curved surface could lead to either an increase or decrease. For example, Tchoul et al [74] showed that the T g of 100 kDa PS tethered (0.03 chains/nm 2 ) to TiO 2 (r = 18 nm, l = 40 nm) decreased by 30°C relative to the bulk, even though TiO 2 is close to a neutral surface to PS. Thermal cleavage of the tethering point restored the T g to that of the bulk, implying the suppression was due to excess free volume arising from frustrated chain packing.…”
Section: Dynamics Of Hnps and Hnp Assembliesmentioning
confidence: 99%
“…Initial studies on TiO 2 /polystyrene HNP systems with high dielectric constants show that the concept is workable, but purity of the final material is critical to maintaining high breakdown fields. [74] For batteries and supercapacitors, ionically conductive electrolytes are desired. HNP-based electrolytes for lithium-ion batteries have higher mechanical strength than pure polymer electrolytes and exhibit superionic conductivities.…”
Section: Prospective Articlesmentioning
confidence: 99%
See 1 more Smart Citation